CORRELATION BETWEEN THE ELECTRONIC STRUCTURE OF QUINAZOLINE DERIVATIVES AND THE ACTIVITY OF THE NTR1 RECEPTOR - Carlos Soloaga Ardiles; Cristian Castro Rodriguez; Julio Surco Luque (Journal of the Chilean Chemical Society, 2020)
SummaryIn this paper, we study the structure-activity relationship between the electronic structure of quinazoline-derived and their inhibitory effect on NTR1 receptor. The methodology used to obtain the results is known as the KPG method (Klopman-Paradejordi-Gómez) has been widely used in recent years. This method is based on obtaining various local reactivity indices, within the Hartree-Fock LCAO-MO and DFT models. The local reactivity indices obtained from the calculations, in conjunction with the reported IC50 values, were subjected to a multiple linear regression analysis corresponding to the most statistically significant equation. These results showed specific sites of the common skeleton, which participate in the activity of the NTR1 recepto, which allowed to propose the pharmacophore that helps to explain in a better way the biological process involved.